Appendicular Lymphoid Hyperplasia in the Differential Diagnosis of Acute Appendicitis: Sonographic Findings. (January 2020) - Whittle, Carolina; Pérez, Lizbet; Cortes, Marcela; Switt, Margarita; Aguirre, Javiera; Castro, Alex
Objectives: To describe sonographic findings of appendicular lymphoid hyperplasia (ALH) and to report demographic data of patients with ALH operated for acute appendicitis (AA). Materials and Methods: In a retrospective study, 694 biopsies of consecutive AA surgeries with previous ultrasonography (US) were reviewed, after selecting the ALH cases. Results: Twenty-five ALH cases were proved histologically (3.8% of appendectomies). The mean age was 13 years, with 84% under 20 years. US findings showed increased appendiceal diameter (average 7 mm) (82%), hypoechogenic pseudonodular mucosal thickening (50%), concentric parietal thickening (13%), and periappendiceal inflammatory changes (18%). In four cases, a normal appendix was noted on US, with two associated with intestinal intussusceptions. Conclusion: ALH is a benign entity most frequent in children that can predispose to AA. Both pathologies can increase the appendiceal diameter. In the pediatric group, ALH could be considered when hypoechogenic pseudonodular appendicular mucosal thickening in the absence of periappendiceal inflammatory changes occurs.